2016
DOI: 10.1007/s40746-016-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management of Vesicoureteral Reflux

Abstract: The past 30 years have seen broad changes in the diagnosis and management of vesicoureteral reflux (VUR). Recently, a clinical debate has generated an open discussion in academic circles. New evidence has shifted treatment patterns away from widespread surgical management and recently brought into question some pharmacologic treatments. VUR is usually not hazardous by itself but is a significant risk factor for urinary tract infection (UTI) and less commonly, renal scarring and insufficiency. Given the costs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
13
1
Order By: Relevance
“…Several bulking agents have been used over the past two decades in the treatment of VUR. In 2001, the US Food and Drug Administration (FDA) approved the use of dextranomer/hyaluronic acid as the first FDA-approved subepithelial injectable treatment for VUR in the USA [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several bulking agents have been used over the past two decades in the treatment of VUR. In 2001, the US Food and Drug Administration (FDA) approved the use of dextranomer/hyaluronic acid as the first FDA-approved subepithelial injectable treatment for VUR in the USA [10].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the substance injected, the endoscopic approach to reflux management is improving, giving better results by time and has gained favor over the past several years over the other treatment options in both Europe (22)(23)(24) and the United States (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that CAP reduces the rate of recurrence of UTI until the reflux resolves. The majority of lower-grade VURs spontaneously resolve as the child grows [26]. Roussey-Kessler et al performed a randomized controlled trial (RCT) of 225 children in which children from ages one month to three years with grade I-III VUR were assigned randomly, to receive daily cotrimoxazole or no treatment and followed up for 18 months [27].…”
Section: Vur and Antibiotic Prophylaxismentioning
confidence: 99%
“…Another significant drawback to CAP is antibiotic resistance. The RIVUR trial demonstrated a substantial amount of resistance to TMP/SMX in patients on prophylaxis with breakthrough UTI compared to the patients on placebo [26].…”
Section: Risks Of Prophylactic Antibioticsmentioning
confidence: 99%